Peran Kementerian/Lembaga Negara untuk Meningkatkan Daya Saing Kepariwisataan Indonesia - Maulana, Addin (Pusat Analisis Keparlemenan Badan Keahlian Sekretariat Jenderal DPR RI, 2022)
The indicator of tourism competitiveness is known as the Travel and Tourism Competitiveness Index (TTCI), published by the World Economic Forum (WEF). TTCI is one of Indonesia’s medium-term development targets for the 2020–2024 period, so it is essential to identify the distribution of roles and contributions of each ministry/ state institution in increasing the competitiveness of Indonesian tourism in the global market. By using a scoring for each TTCI sub-pillar indicator, this study aims to map the role of each ministry/state institution in the competitiveness of Indonesian tourism in the global market. This study resulted in recommendations for the Indonesian House of Representatives (DPR RI) through its supervisory function in encouraging ministries/state institutions to disseminate information to regional tourism stakeholders regarding how to view competitive and sustainable tourism development based on the TTCI indicator. The DPR RI also needs to slightly encourage the existing indicators to be included in the performance target indicators of the relevant ministries/state institutions. Primary data indicators also need to be considered by publishing development achievements to the public to harmonize government development achievements with public perceptions as recipients of these development outcomes. Thus, the synergy in achieving the competitiveness target can be materialized optimally. Abstrak Indikator daya saing kepariwisataan dunia yang dikenal dengan Travel and Tourism Competitiveness Index (TTCI) diterbitkan oleh World Economic Forum (WEF) sebagai tolok ukur daya saing pariwisata secara global. Peningkatan TTCI merupakan salah satu target pembangunan jangka menengah Indonesia periode 2020–2024 sehingga penting untuk dapat mengidentifikasi sebaran peran dan kontribusi dari setiap kementerian/lembaga negara dalam meningkatkan daya saing kepariwisataan Indonesia di pasar global. Dengan menggunakan pembobotan pada setiap indikator subpilar TTCI, kajian ini bertujuan untuk memetakan peran setiap kementerian/lembaga negara dalam daya saing kepariwisataan Indonesia di pasar global. Kajian ini mengidentifikasi bahwa terdapat 17 mitra strategis Kementerian Pariwisata dan Ekonomi Kreatif dalam membentuk daya saing kepariwisataan. Kajian ini merekomendasikan kepada Dewan Perwakilan Rakyat Indonesia (DPR RI) melalui fungsi pengawasan untuk mendorong kementerian/lembaga agar melakukan sosialisasi kepada pemangku kepariwisataan daerah terkait bagaimana cara memandang pembangunan kepariwisataan yang berdaya saing dan berkelanjutan berbasis pada indikator TTCI. DPR RI juga perlu mendorong agar indikator-indikator yang ada masuk ke dalam capaian indikator sasaran kinerja kementerian/lembaga terkait. Penting juga bagi kementerian/lembaga untuk memperhatikan indikator data primer dengan melakukan publikasi capaian-capaian pembangunan pada publik guna menyelaraskan capaian pembangunan pemerintah dengan persepsi masyarakat sebagai penerima manfaat dari hasil pembangunan. Dengan demikian, maka sinergi dalam pencapaian target daya saing dapat terlaksana secara optimal.